AB0635 Patient Reported Outcomes and Acute Phase Reactants in Polymyalgia Rheumatica in Patients Treated with Prednisone Versus Modified-Release Prednisone. (9th June 2015) - Betelli, M.; Erba, G.; Valena, C.; Ricci, M.; Allevi, E.; Riva, M.; Barbarossa, S.; Bonomi, F.; Grosso, G.; Pozzi, M.R.
Abstract : Background: Polymyalgia rheumatica (PMR) is a chronic inflammatory disorder of the elderly, characterised by morning stiffness, pain and aching in the hip and shoulder girdles and acute phase reactants increase. The response to low-dose prednisone (Pd) is marked and fast on both Patient Reported Outcomes (PROs) and acute phase reactants, but most patients require a treatment course of 1–3 years. A new modified-release delivery system Prednisone adapts the release of the administered glucocorticoid to the circadian rhythms and proved to be useful for morning stiffness, fatigue and disease activity control in Rheumatoid Arthritis. Objectives: We compared immediate release Prednisone (Pd) to modified release Prednisone (MR-Pd) on PROs and acute phase reactants in Polymyalgia Rheumatica. Methods: We studied 15 patients (5 men, mean age 70 years, SD 8.25) with newly diagnosed PMR and previously untreated. They received the same tapering dose of prednisone starting from 15 mg: 8 patients received a MR-Pd tablet, and 7 a Pd tablet. We observed no drop-outs but only nine patients have completed the 52-week assessment period by now (3 men, mean age 74.5 years, SD 5.22). CRP/ESR, VAS for stiffness duration/intensity and fatigue and HAQ-DI (PROs) were obtained at baseline and at week 4 and 52. We assessed disease activity using the score by Leeb et al. 1, and we used Standardized Response Means (SRM), a measure of responsiveness, to evaluate acute phase response and clinical parameters improvement at week 4 and 52. Results: All patients showed a decrease on disease activity within 4 and 52 weeks, and the mean relative changes of the CRP/ESR and PROs from baseline to 4th and 52th week were not statistically different between Pd and MR-Pd (p>0.05), confirming their same efficacy at the same dosage. We noticed that after 4 weeks CRP, fatigue, stiffness duration and HAQ assessment showed a better response in the group treated with MR-Pd (CRP SRM 1.05-0.73, fatigue SRM 0.85-0.62; stiffness duration 1.28–0.67, HAQ SRM 1.41-1.17 for MR-Pd and Pd respectively), while immediate release Prednisone was more effective on stiffness intensity (SRM 1.43–1.11). At week 52, the two different groups of patients had a comparable total intake of steroids (1.986 g for MR-Pd group, and 1.860 g for Pd group); both the formulations were highly effective on all disease parameters, but there were no significantly differences regarding ESR, CRP, fatigue, stiffness intensity (ESR SRM 1.67–1.34, CRP SRM 0.88–0.99, fatigue SRM 1.46–1.27, stiffness intensity 2.39–2.84 for MR-Pd and Pd respectively), whereas VAS, stiffness duration and HAQ improved in patients treated with MR-Pd (VAS SRM 3.39–2.34, stiffness duration SRM 3.38–1.14, HAQ SRM 3.22–1.77). Conclusions: Modified-Release Prednisone and Immediate Release Prednisone showed the same overall efficacy on Patient Reported Outcomes and acute phase reactants in patients with PMR, but with different timings and impacts on various disease aspects. References: Leeb B, et al, The Polymyalgia Rheumatica Activity Score in Daily Use: Proposal for a Definition of Remission. Arthritis & Rheumatism 2007;5:810-815. Disclosure of Interest: None declared